Maximizing content of Omega-3 (EPA and DHA) in the process of enzymatic acidolysis of canola oil and concentrated of long-chain polyunsaturated fatty acids (LCPUFA) in supercritical CO2 conditions - Cedano, José (2016)
The aim of this study was to optimize the content of EPA and DHA in the process of enzymatic acidolysis of canola oil and concentrated of long-chain polyunsaturated fatty acids (LCPUFA) in structured triacylglycerols (TAGs). For this purpose, nonspecific lipase B from Candida antarctica immobilized in a supercritical CO2 was used. Crude salmon oil obtained from the industrial byproducts was used to obtain LCPUFA concentrate. Initially, a LCPUFAs concentrate was obtained by basic hydrolysis and posterior complexation with urea. Subsequently the process variables were optimized enzymatic acidolysis were optimized using a central composite rotational design 25-1 + star, with 5 factors and 30 experimental trials, based on the response surface methodology. The optimal conditions that maximized the content of EPA and DHA to 3.92 g/100 g TFA and 9.09 g/100 g TFA, respectively in the purified TAGs corresponded to a LCPUFA percentage 71.71% and canola oil percentage 28.29%, temperature 57.8 °C, pressure 172.0 bar, time 23.97 h enzyme percentage of 7.74%.